Natural variability of lung function in young healthy school children. Issue 2 (13th April 2016) - Kirkby, Jane; Bountziouka, Vassiliki; Lum, Sooky; Wade, Angie; Stocks, Janet
Knowledge about long-term variability of lung function in healthy children is essential when monitoring and treating those with respiratory disease over time. The aim of this study was to define the natural variability in spirometry in young children after an interval of 12 months. The Size and Lung function In Children study was a prospective study designed to assess spirometry and body size, shape and composition in a multi-ethnic population of London school children. 14 schools with a wide range of socioeconomic circumstances were recruited. Spirometric and anthropometric assessments and parental questionnaires pertaining to respiratory symptoms, previous medical history, pubertal status and socioeconomic circumstances were completed at baseline and ∼1 year later. Technically acceptable spirometry data on two occasions ∼1 year apart (range 9–16 months) were available in 758 children (39% boys, mean±sd age 8.1±1.6 years), 593 of whom were classified as "healthy". Mean±sd within-subject between-test variability was 0.05±0.6 z-scores, with 95% of all the children achieving a between-test variability within ±1.2 z-scores (equating to ∼13% predicted). Natural variations of up to 1.2 z-scores occur in healthy children over ∼1 year. These must be considered when interpreting results from annual reviews in those with lung disease who are otherwise stable, if unnecessary further investigations or changes in treatment are to be avoided. Spirometry can vary by up to 1.2 z-scores over the course of 1 year in children without any overt lung disease http://ow.ly/YZ7mT